A water additive with pomegranate can reduce dental plaque and calculus accumulation in dogs - Gawor, Jerzy P.; Ziemann, Daria; Nicolas, Celine S. (Frontiers in Veterinary Science, 2023)
Oral homecare plays a major part in dental disease prevention but it can be difficult to perform and time-consuming. Furthermore, the product used can be of limited efficiency. The goal of this study was to assess the efficacy of a water additive to limit the accumulation of plaque and calculus in dogs. Forty dogs were selected and randomly allocated to one of the two groups after scaling and polishing on day 0. The control group received no oral hygiene while the second group received the water additive (Vet Aquadent® FR3SH™, Virbac) every day. After 30 days, plaque and calculus accumulations were evaluated under anesthesia. The Gingival Bleeding Index (GBI) was assessed on days 0 and 30. On day 30, the plaque and calculus indices were significantly smaller (p<0.05) in the Aquadent group compared to the control group with median (Q1-Q3) scores of 1.22 (0.99-1.44) vs. 2.31 (1.65-3.86), respectively for plaque and 0.25 (0.15-0.42) vs. 0.33 (0.32-0.69) for calculus. Between day 0 and day 30, the GBI significantly decreased in the control group [from 0.39 (0.21-0.56) to 0.19 (0.08-0.29)] and in the Aquadent group [from 0.33 (0.18-0.47) to 0.00 (0.00-0.00)] but the decrease was significantly greater in the Aquadent group. These results show for the first time that the water additive tested can reduce dental deposit accumulation in dogs and improve gingival health. It can be recommended after a dental cleaning, especially to owners who are reluctant to provide dental care at home due to a lack of time or convenience.